MEDIA PEMBELAJARAN SEPAK BOLA BERBASIS APLIKASI “BOLA PINTAR” UNTUK SEKOLAH DASAR - Jeffry Trinando; Feri Yose Rizal; Muhammad Fathan Arisyi; Ade Fitri Ariska; Endang Sri Hevina; Herudi Lubis; Reza Hadinata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the effectiveness of application-based soccer learning media for elementary school students. This learning media is designed to assist physical education teachers in delivering basic soccer technique materials in an interactive and interesting way. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of 60 students in grades 4-6 of elementary school and 6 physical education teachers in 3 elementary schools in City X. The results showed that the developed application received a